ANALISIS KEGIATAN PRAKTIK PENGALAMAN LAPANGAN (PPL) MAHASISWA PGSD PADA KELAS ATAS SEKOLAH DASAR: STRATEGI, TANTANGAN, DAN REFLEKSI PEDAGOGIS - Ananda Nurhabibah; Moh. Daufir Rahman; Dani Rifky Fitra (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe instructional strategies, identify challenges, and analyze the pedagogical reflections of PGSD students during the implementation of Field Teaching Practice (PPL) in upper-grade elementary school classes. This research employed a descriptive qualitative approach with a case study design. The data were obtained from students’ teaching experience reports in grades 4, 5, and 6. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing, with source triangulation to ensure data validity. The results show that the instructional strategies applied include group discussions, problem-based learning, contextual teaching, as well as the use of Higher Order Thinking Skills (HOTS)-based worksheets and interactive media. The challenges faced include differences in students’ critical thinking abilities, classroom management dynamics, and fluctuating learning motivation. The pedagogical reflections indicate an improvement in students’ understanding of the importance of adaptive, creative, and student-centered learning. This study confirms that PPL in upper-grade classes plays an important role in developing the pedagogical and professional competencies of prospective elementary school teachers.